Impact of filtration elements on bioelectrical signal; IOP Conference Series: Materials Science and Engineering; Vol. 124 : Mechanical Engineering, Automation and Control Systems (MEACS2015) - Grigoriev M. V. Mikhail Vladimirovich (Numerical Simulation of Applied Problems, 2016)
Title screen